2016
DOI: 10.1016/j.bbmt.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Alternative-Donor Hematopoietic Stem Cell Transplantation with Post-Transplantation Cyclophosphamide for Nonmalignant Disorders

Abstract: Allogeneic (allo-) hematopoietic stem cell transplant (HSCT) is curative for many nonmalignant pediatric disorders, including hemoglobinopathies, bone marrow failure syndromes, and immunodeficiencies. There is great success using HLA-matched related donors for these patients; however, the use of alternative donors has been associated with increased graft failure, graft versus host disease (GVHD), and transplant-related mortality (TRM). HSCT using alternative donors with post-transplantation cyclophosphamide (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
64
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 36 publications
4
64
1
Order By: Relevance
“…Klein et al recently reported on their experience with 11 pediatric patients carrying a host of life-threatening nonmalignant diseases, who all received reduced-intensity–conditioned transplantation with alternative donors (including 4 haploidentical donors) and PT/Cy alone or in combination with tacrolimus and mycophenolate mofetil [46]. In their series, there was only limited acute GVHD, no transplantation-related mortality, and successful engraftment, leading to reversal of the disease manifestations in all patients [46].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Klein et al recently reported on their experience with 11 pediatric patients carrying a host of life-threatening nonmalignant diseases, who all received reduced-intensity–conditioned transplantation with alternative donors (including 4 haploidentical donors) and PT/Cy alone or in combination with tacrolimus and mycophenolate mofetil [46]. In their series, there was only limited acute GVHD, no transplantation-related mortality, and successful engraftment, leading to reversal of the disease manifestations in all patients [46].…”
Section: Discussionmentioning
confidence: 99%
“…Klein et al recently reported on their experience with 11 pediatric patients carrying a host of life-threatening nonmalignant diseases, who all received reduced-intensity–conditioned transplantation with alternative donors (including 4 haploidentical donors) and PT/Cy alone or in combination with tacrolimus and mycophenolate mofetil [46]. In their series, there was only limited acute GVHD, no transplantation-related mortality, and successful engraftment, leading to reversal of the disease manifestations in all patients [46]. Parta et al also described a child with chronic granulomatous disease who underwent haploidentical transplantation utilizing PT/Cy for GVHD prophylaxis who had successful engraftment and limited acute GVHD (grade 2) and CMV viremia, both of which were well controlled [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful allogeneic HSC or BM transplantation relies heavily on the ability of the HLA-matched donor cells to replace the recipient's hematopoietic functions by homing and engrafting into the host BM niche (7)(8)(9). Currently, all transplantations require recipient conditioning, which involves cytoreductive agents and/or irradiation to improve donor cell engraftment (10)(11)(12). The conditioning provides immunosuppression and allows for donor cells to engraft in the recipient HSC niche (12,13).…”
mentioning
confidence: 99%